Stock market development: A~reflection of governance regulatory framework in Nigeria - Fisayo Fagbemi; Opeoluwa Adeniyi Adeosun; Kehinde Mary Bello (Journal of Capital Markets Studies (JCMS), 2022)
Purpose - The article examines the possible long-run and short-run impact of regulatory quality on stock market performance in Nigeria for 1996-2019 period. Design/methodology/approach - The study adopts autoregressive distributed lag (ARDL) bounds test and cointegrating regression techniques. Findings - Findings reveal that regulatory quality positively and significantly influences the performance of stock market, which strengthens the view that market-enhancing governance can engender an improvement in stock market performance. The study further demonstrates that quality of the regulatory environment is a critical component of market operations, since the improvement of the operation of stock market performance depends on appropriate policy measures, which could be the outcome of improved governance. Practical implications - It is suggested that, while improving the institutional environment is a challenge to regulators, there is need for strong and effective regulatory mechanism to enhance the development of stock market in the country. Originality/value - Based on the two competing hypotheses and limited attention, previous studies accorded the role of regulatory quality in the performance of stock market in the context of Nigeria. This study assessed the gap in the literature by taking the task of validating the impact of regulatory quality on stock market development.
Keywords: 330; ARDL; Business environment; Nigeria; Regulatory quality; Stock market performance